X-ray microtomographic characterization of highly rough titanium cold gas sprayed coating for identification of effective surfaces for osseointegration. (8th July 2019) - Vilardell, A M; Cinca, N; Barriuso, E; Frigola, J; Dosta, S; Cano, I G; Guilemany, J M
Abstract: A highly rough titanium coating obtained by Cold Gas Spray (CGS) has been characterized by means of high-resolution 3D microtomography (micro-CT) with the aim to evaluate its open and close porosity for possible use in orthopaedic implants to promote osseointegration. Micro-CT allowed a qualitative and quantitative description of the main features, morphology of the pores and surface roughness of the coating. Several numerical values were obtained to describe size, form and distribution of the closed/inner and open/outer pores. Additionally, surface roughness and open porosity were image-analyzed to find the effective surface for osseointegration.